Single-cell transcriptomic profiling identifies TIMP1 as a diagnostic marker linked to macrophage ferroptosis in ulcerative colitis - Wen-Hao Xiong; Shuo Huang; Yan-Hong Liu; Guo-Shan Chen; Dan-Zhou Li; Yong-Cheng Di; Wen-Bin Song; Yong-Chao Zhang; Yi-Fan Wang; Feng Qi (Tissue and Cell, 2026)

Influence of tea-derived polyphenols architecture on the structural, functional and allergenicity properties of β-lactoglobulin: A comparison of non-covalent and covalent interactions - Zhi-Wei Liu; Jia-Wei Zou; Xiu-Bin Liu; Waqar Ahmed; Rana Muhammad Aadil; Marwa Ezz El-Din Ibrahim; Jun-Hu Cheng; Xie-Ling He; Hou-Gang Zhou; Hong-Ying Guo (Food Research International, 2026)

The influence of replacing soybean meal with corn gluten meal on the digestive and absorptive capacity and amino acid metabolism of sub-adult grass carp (Ctenopharyngodon idella) - Yan Liu; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Wen-Jie Tang; Cheng-Bo Zhong; Pei Wu (Aquaculture, 2026)

Re-appraisal of the Mesozoic male cone Ixostrobus Raciborski (Czekanowskiales) based on new material from the Qaidam Basin, NW China: New insights into systematics, diversity and spatio-temporal distribution - Hong-Yu Chen; Yong-Dong Wang; Li Zhang; Yan-Bin Zhu; Ao-Wei Xie; Peng-Cheng An; Dieter Uhl (Review of Palaeobotany and Palynology, 2026)

Sesquiterpenoids from the fruits of Alpinia oxyphylla showing renal protective activity through NF-κB/IκBα and TGF-β1/Smad signaling pathways - Bo-Tao Lu; Xiao-Ning Liu; Hong-Bin Fang; Yue-Tong Zhu; Yu-Zhong Zheng; Yong-Xian Cheng; Yan-Zhi Wang (Phytochemistry, 2026)

Sensitive fluorescent europium-organic framework sensor for selective discrimination of tetracycline and norfloxacin and applications in food samples - Chaodan Xiong; Liping Ren; Qiu-Hong Cheng; Xiang-Yu Zhang; Lijuan Liang; Kun Huang; Da-Bin Qin (Food Chemistry, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Impacts of microplastics on soil quality and productivity: Analysing shape- and dose-dependent responses - Peng-Yang Wang; Xiao-Bin Xiong; Jia-Cheng Guo; Hong-Yan Tao; Wen-Ying Wang; Muhammad Ashraf; Sheng-Jun Ji; Ze-Ying Zhao; Chang-Lang Yang; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2026)

A Survey of the Species Origins of Common Fish Cell Lines—With a Particular Focus on the Grass Carp Ovarian Cell Line ( GCO ) - Hong Yang; Mijuan Shi; Yingyin Cheng; Wanting Zhang; Bin Gui; Rong Huang; Yaping Wang; Xiao‐Qin Xia (Journal of Fish Diseases, 2026)
Cell line misidentification or contamination undermines the reliability of research outcomes. In this study, we verified the species origin of commonly used fish cell lines, with a particular focus on the grass carp ovarian cell line (GCO). RNA‐seq data from 146 samples of 11 widely used fish cell lines were collected from public databases (NCBI‐SRA) and were mapped to the reference genomes of eight species. GCO RNA‐seq samples from three Chinese laboratories showed a mapping rate of 21.64% ± 3.61% to the grass carp genome, but 89.81% ± 4.83% to the fathead minnow genome. Further transcriptomic similarity analysis revealed that these GCO RNA‐seq samples clustered more closely with cell lines originating from fathead minnow. Targeted analysis of the COI gene amplification region confirmed that nearly all reads from GCO RNA‐seq samples mapped exclusively to the fathead minnow COI amplicon. Collectively, these results indicate that GCO may have undergone cross‐contamination or species misidentification. This study raises doubts about the true species origin of the GCO cell line and proposes that COI DNA barcoding can be used to discriminate the species origin of fish cell lines.

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

Endoplasmic Reticulum Stress in the Keratinocytes Contributes to Chronic Itch by Activation of Lipocalin 2/MC4R/TRPV1 Pathway - Wei Ge; Yu Feng; Li Zhang; Qian-Liang Wang; Cheng-Wei Zhang; Zhi-Hong Wang; Guo-Kun Zhou; Shi-Yu Sun; Xiu-Hua Miao; Tong Liu; Bin Wu; Jun Yan (Neuroscience Bulletin, 2026)

Origin, evolution and precipitation mechanism of ore-forming fluids in Jiaojia belt, Jiaodong Peninsula: Insights from trace elements and S Fe isotopes of pyrite - Jinyu Cheng; Lin Yang; Qingfei Wang; Yixin Li; Wen Zhang; Bin Sun; Xue Dong; Shiyu Zhao; Dapeng Li; Kexin Zhao; Hong Wang (Journal of Geochemical Exploration, 2026)

Novel Models to Predict Pregnancy for Patients Receiving In-Vitro-Fertilization Embryo Transfer: The Significance of Clinical Indicators and Key Gene Expression in the Endometrium - Cheng Shi; Yan-Bin Wang; Huan Shen; Fu-Mei Gao; Min Fu; Xi Chen; Hong-Jing Han (Biochemical Genetics, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Enhanced hydrolysis of cellobiose using vanadium-doped niobium phosphate: A water-tolerant solid acid catalyst with superior kinetic performance - Da-Ming Gao; Jianxing Zheng; Cheng-Bin Hong; Tong Wang; Xue-Chen Xu; Hidemi Fujino; Haichao Liu (Fuel, 2026)

A Conserved Bactericidal Permeability-Increasing Protein (BPI) Mediates Immune Sensing and Host Defense in the Hong Kong Oyster (Crassostrea hongkongensis) - Laiba Shafique; Yuwei Zhao; Muhammad Farhan Khan; Cheng Huang; Li Li; Peng Zhang; Peng Zhu; Da Zeng; Xueyu Yan; Bin Gong; Yongyan Liao; Youhou Xu; et al. (Fishes, 2026)
The bactericidal permeability-increasing protein (BPI) and lipopolysaccharide binding protein (LBP) are fundamental to innate immunity. However, their functional diversity and evolutionary conservation in ecologically crucial invertebrates, such as oysters, remain largely understudied. In this study, we identify and characterize a novel homolog of BPI/LBP, designated as ChBPI/LBP in the Hong Kong oyster (Crassostrea hongkongensis). Through structural and phylogenetic analysis, we identify ChBPI/LBP as a distinct member of the BPI protein family, with a high isoelectric point (pI of 9.26), indicating potent cationic BPI-like bactericidal function. We found that ChBPI/LBP is constitutively highly expressed at mucosal sites such as the gills and is rapidly upregulated in hemocytes following a challenge with Aeromonas hydrophila. Recombinant ChBPI/LBP demonstrated potent and specific bactericidal activity against Gram-negative pathogens. These findings suggest that ChBPI/LBP is an important antimicrobial peptide (AMP) effector in the oyster’s immune response. This work provides novel perspectives on the evolutionary mechanisms of innate immunity in bivalves and may have implications for disease management in aquaculture.

Diagenesis and burial history controls on Oligocene Huagang sandstones, southern Xihu Sag (East China Sea Basin): Implications for the formation of effective reservoirs - Hong-Liang Huo; Cheng-Lin Liu; Dao-Wu Huang; An-Qi Tian; Rizwan Sarwar Awan; Hong-Yan Gao; Chuang-Xin Liu; Xue-Yong Chen; Zi-Ye Tian; Tao-Zheng Yang; Bin-Bin Liu; Chao-Jun Liang (Marine and Petroleum Geology, 2025)

Continental growth in eastern Central Asian Orogenic Belt: Evidence from Middle Permian–Middle Jurassic magmatism - Hong-Yan Wang; Jian-Bo Zhou; Peter A. Cawood; Bin Huang; Zi-Yi Zhu; Cheng-Qiang Li; Gong-Yu Li (Earth-Science Reviews, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

Nitrogen-doped hydrothermal carbon as a catalyst for selective alkoxyphenol production from pine pyrolysis - Dong-hong Nan; Cheng-bo Zhang; Qi Niu; Shi-yu Feng; Bin Hu; Ji Liu; Kai Li; Qiang Lu (Biomass and Bioenergy, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

Postnatal exposure to various benzophenones at environmentally relevant levels enhances the susceptibility of mammalian testes to cyclophosphamide-induced spermatogenic stress in adulthood - Yan-Rong Gao; Ya-Jia Pu; Yu-Xin Sheng; Bin Cheng; Li-Jie Wang; Ya-Nan Tian; Jing Pu; Hui-Ming Ma; Hong-Mei Li; Hai-Ming Xu (Environmental Pollution, 2025)

Effect of anticyclonic eddies on the production and emission of marine dimethylsulfide in the northern South China Sea - Jin-Wei Wu; Feng Xu; Shi-Bo Yan; Gao-Bin Xu; Yu-Cheng Jiang; Xiao-Ran Li; Xing Zhai; Li-Min Zhou; Hong-Hai Zhang; Zhao-Hui Chen (Global and Planetary Change, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Machine learning strategy secures urban smart drinking water treatment plant through incremental advances - Yu-Qi Wang; Hong-Cheng Wang; Zi-Jie Xiao; Ling-Jun Bu; Jiuling Li; Xiao-Chi Feng; Bin Liang; Wen-Zong Liu; Fei-Yun Sun; Shi-Qing Zhou; Ai-Jie Wang (Water Research, 2025)

Organic fertilizer mitigated the oxidative stress of tomato induced by nanoplastics through affecting rhizosphere soil microorganisms and bacteriophage functions - Liang-Bin Zhao; Zi-Xuan Tang; Hui-Fang Zhai; Hong-Yu Lai; Hai-Yang Li; Shuo Liu; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Application of sourdough in gluten-free bakery products - Hangyan Dan; Hongyu Li; Cheng Li; Zhengfeng Fang; Bin Hu; Hong Chen; Caixia Wang; Saiyan Chen; Teng Hui; Wenjuan Wu; Zhen Zeng; Yuntao Liu (Critical Reviews in Food Science and Nutrition, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Coordinate the environmental and economic sustainability in a closed-loop supply chain - Bin Wang; Hong Cheng; Hangsheng Yang (Journal of Environmental Management, 2025)

Fermentation of highly toxic reed hydrolysate using Candida glycerinogenes to produce platform compound glycerol - Yiwen Cheng; Liya Zhang; Dongqi Jiang; Mengying Wang; Xueqing Du; Hong Zong; Xinyao Lu; Bin Zhuge (International Biodeterioration & Biodegradation, 2025)

Reactions of oxazepam with two typical water treatment oxidants in aqueous solutions: Results based on density functional theory - Ling-Ling Zhang; Hong-Yu Dai; Tao Peng; Xiao-Yuan Liu; Zhi-Cheng Zhou; Chao Xu; Bin Yang; Guang-Guo Ying (Chemosphere, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Boosting structural stability and air stability towards layered oxide cathodes for potassium ion batteries - Hong Chen; Lu-Kang Zhao; Xuejiao Cheng; Xuan-Wen Gao; Zhaomeng Liu; She-Dong Li; Dong-Run Yang; Tian-Zhen Ren; Wen-Bin Luo (Chemical Engineering Journal, 2025)

Chemical constituents from Bambusae concretio Silicea and their anti-renal fibrosis activity - Hong Zhou; Ye-Fei Chen; Bin-Yuan Hu; Qing-Qian Zeng; Yong-Xian Cheng (Phytochemistry Letters, 2024)

Development and validation of a potential risk area identification model for hand, foot, and mouth disease in metropolitan China - Xu Guang; Yifei He; Zhigao Chen; Hong Yang; Yan Lu; Jun Meng; Yanpeng Cheng; Nixuan Chen; Qingqing Zhou; Rongxin He; Bin Zhu; Zhen Zhang (Journal of Environmental Management, 2024)

Blood cadmium levels and overactive bladder in middle-aged and older adults in the United States: Insights from NHANES 2007–2020 data - Fan Gao; Yin Lu; Qiang Cheng; Qing Ai; Bin Jiang; Zhen-Jun Luo; Guo-Rong Yang; Kai-Kai Lv; Qing Yuan; Hong-Zhao Li (Environmental Pollution, 2024)

Selective hydrogenolysis of glycerol toward 1-propanol and 1,2-propanediol via tuning the reduction temperature of (Mn)/Pt/WOx catalysts - Mingwei Zhang; Cheng-Bin Hong; Zhaoying Ding; Yujing Weng; Honghui Gong; Haiyong Wang; Yulong Zhang; Yuhe Liao; Haichao Liu (Chemical Engineering Journal, 2024)

Magnetic nanochain-induced anisotropic nerve assembly for spinal cord injury repair - Yangnan Hu; Hao Wei; Hui Zhang; Hong Cheng; Dongyu Xu; Huan Wang; Zeyou Zhang; Bin Zhang; Yixian Liu; Yusong Wang; Chen Zhang; Jilai Li; et al. (Chemical Engineering Journal, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

NOx precipitation and valorization driven by photocatalysis and adsorption over red soil - Xueqin Xu; Ram Kumar Shrestha; Jiawang Shu; Hong Cheng; Guang Yang; Jiupai Ni; Mengyun Hu; Bin Li; Pei Zheng; Heping Zeng; Chengsheng Ni (Science of The Total Environment, 2024)

Cold plasma for enhancing covalent conjugation of ovalbumin-gallic acid and its functional properties - Chang Liu; Pan-Pan Tang; Xiu-Bin Liu; Jun-Xiang Liu; Xiao-Hong Pan; Rana Muhammad Aadil; Jun-Hu Cheng; Zhi-Wei Liu (Food Chemistry, 2024)

In vivo EPID-based daily treatment error identification for volumetric-modulated arc therapy in head and neck cancers with a hierarchical convolutional neural network: a feasibility study - Yiling Zeng; Heng Li; Yu Chang; Yang Han; Hongyuan Liu; Bo Pang; Jun Han; Bin Hu; Junping Cheng; Sheng Zhang; Kunyu Yang; Hong Quan; et al. (Physical and Engineering Sciences in Medicine, 2024)

Experimental and analytical study on the mechanical response of shield tunnel segmental linings strengthened by a steel-UHPC composite - Ren-Peng Chen; Meng Fan; Hong-Zhan Cheng; Huai-Na Wu; Yang Zhang; Shi-Qiang Ruan; Bin-Yong Gao (Tunnelling and Underground Space Technology, 2024)

Enhancing the sodium-ion storage performance of two-dimensional layered Ti3CN with a molecular riveting strategy - Dong-Ting Zhang; Hong-Yan Li; Wen-Jie Shi; Yu-Xia Hu; Ling-Bin Kong; Xue-Feng Lu; Zi-Zhou Yuan; Mao-Cheng Liu (Chemical Engineering Journal, 2024)

Rapid detection of multiple phytoplasmas with an All-In-One Dual (AIOD) CRISPR assay - Qicheng Li; Sicheng Guo; Jidong Li; Jian Jiao; Qiqi Yang; Jia Yao; Yun Chen; Xia Ye; Jun Cheng; Bin Tan; Xianbo Zheng; Yingxia Wu; et al. (Crop Protection, 2024)

Regulating microbial redox reactions towards enhanced removal of refractory organic nitrogen from wastewater - Ke Shi; Bin Liang; Hao-Yi Cheng; Hong-Cheng Wang; Wen-Zong Liu; Zhi-Ling Li; Jing-Long Han; Shu-Hong Gao; Ai-Jie Wang (Water Research, 2024)

Corrigendum to “Test and design of rectangular steel-reinforced concrete-filled stainless steel tubular short columns” [Eng Struct 293 (2023) 116689] - Zhi-Bin Wang; Hong-Wei Dai; Cheng-Liang Ke (Engineering Structures, 2024)

Aptamer based hybrid monolithic pipette tips supported by melamine sponge for enrichment of proteins - Yue-lun Sun; Jie Cheng; Bin-bin Liu; Jun-qin qiao; Ling-yu Zhao; Hong-zhen Lian; Li Mao (Analytica Chimica Acta, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

SMC-5/6 complex subunit NSE-1 plays a crucial role in meiosis and DNA repair in Caenorhabditis elegans - Arome Solomon Odiba; Chiemekam Samuel Ezechukwu; Guiyan Liao; Ye Hong; Wenxia Fang; Cheng Jin; Anton Gartner; Bin Wang (DNA Repair, 2024)

Characterization of three novel stem rot pathogens and their antagonistic endophytic bacteria associated with Cistanche deserticola - Xin-Yi Zhou; Ya-Li Ban; Cheng-Bin Wang; Xin-Tao Chen; Hong-Wang Yang; Yong-Jun Feng (Archives of Microbiology, 2024)

Dimeric diarylheptanoids with anti-inflammatory activity from Zingiber officinale - Hong-bin Fang; Ying-Ying Si; Hui-Ying Niu; Yong-Ming Yan; Wei-sheng Feng; Yong-Xian Cheng; Yan-Zhi Wang (Phytochemistry, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Machine learning framework for intelligent aeration control in wastewater treatment plants: Automatic feature engineering based on variation sliding layer - Yu-Qi Wang; Hong-Cheng Wang; Yun-Peng Song; Shi-Qing Zhou; Qiu-Ning Li; Bin Liang; Wen-Zong Liu; Yi-Wei Zhao; Ai-Jie Wang (Water Research, 2023)

Exposure to polycyclic aromatic hydrocarbons (PAHs) in outdoor air and respiratory health, inflammation and oxidative stress biomarkers: A panel study in healthy young adults - Huilin Zhang; Ranran Liu; Liu Yang; Hong Cheng; Shengchun Wang; Bin Zhang; Jiyuan Shao; Shengtao Ma; Dan Norbäck; Xin Zhang; Taicheng An (Science of The Total Environment, 2023)

Unusual acetylated flavonol glucuronides, oxyphyllvonides A−H with renoprotective activities from the fruits of Alpinae oxyphylla - Yue-Tong Zhu; Hong-Bin Fang; Xiao-Ning Liu; Yong-Ming Yan; Wei-Sheng Feng; Yong-Xian Cheng; Yan-Zhi Wang (Phytochemistry, 2023)

Succipenoids A-C: A dimeric abietane and nor-abietane diterpenoids from fossil Chinese medicinal succinum and their anti-inflammatory potential - Yun-Fei Wang; Hong-Bin Fang; Yong-Ming Yan; Yong-Xian Cheng (Phytochemistry, 2023)

Solvent-exchange triggered hydrogen bond activation strategy toward self-adaptive strong and tough organohydrogel artificial muscle - Xiang-Jun Zha; Bin Zhang; Zhi-Cheng Cheng; Sheng Zhang; Jun-Hong Pu; Ji-Gang Huang; Wei Yang (Chemical Engineering Journal, 2023)

Dampness and mould in Chinese homes and sick building syndrome (SBS) symptoms – Associations with climate, family size, cleaning and ventilation - Bin Zhang; Dan Norbäck; Hong Cheng; Baizhan Li; Yinping Zhang; Zhuohui Zhao; Qihong Deng; Chen Huang; Xu Yang; Chan Lu; Hua Qian; Tingting Wang; et al. (Building and Environment, 2023)

Correction: Microglial Depletion does not Affect the Laterality of Mechanical Allodynia in Mice - Quan Ma; Dongmei Su; Jiantao Huo; Guangjuan Yin; Dong Dong; Kaifang Duan; Hong Cheng; Huiling Xu; Jiao Ma; Dong Liu; Bin Mou; Jiyun Peng; et al. (Neuroscience Bulletin, 2023)

Nine pairs of undescribed enantiomers from the resin of Styrax tonkinensis (Pierre) Craib ex Hart with anti-inflammatory activity - Qun Li; Hong-Bin Fang; Bin-Yuan Hu; Yong-Ming Yan; Ya-Bin Jiao; Gan-Peng Li; Yong-Xian Cheng (Phytochemistry, 2023)

Exploring HONO formation and its role in driving secondary pollutants formation during winter in the North China Plain - Shaobin Zhang; Guo Li; Nan Ma; Yao He; Shaowen Zhu; Xihao Pan; Wenlin Dong; Yanyan Zhang; Qingwei Luo; Jeannine Ditas; Uwe Kuhn; Yuxuan Zhang; et al. (Journal of Environmental Sciences, 2023)

Preparation and characterization of inclusion complex of Myristica fragrans Houtt. (nutmeg) essential oil with 2-hydroxypropyl-β-cyclodextrin - Xiaohui Xi; Jialing Huang; Shengyang Zhang; Qian Lu; Zhengfeng Fang; Cheng Li; Qing Zhang; Yuntao Liu; Hong Chen; Aiping Liu; Shuxiang Liu; Caixia Wang; et al. (Food Chemistry, 2023)

Test and design of rectangular steel-reinforced concrete-filled stainless steel tubular short columns - Zhi-Bin Wang; Hong-Wei Dai; Cheng-Liang Ke (Engineering Structures, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Targeting transportation of curcumin by soybean lipophilic protein nano emulsion: Improving its bioaccessibility and regulating intestinal microorganisms in mice - Zhen Zeng; Siqi Deng; Yang Liu; Cheng Li; Zhengfeng Fang; Bin Hu; Hong Chen; Caixia Wang; Saiyan Chen; Wenjuan Wu; Yuntao Liu (Food Hydrocolloids, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Mid-Neoproterozoic tectonic switch from orogeny to intraplate extension in NW Tarim Craton: New evidence from a composite dike of the Aksu Group - Hong-Xiang Wu; Feng-Qi Zhang; Yildirim Dilek; Han-Lin Chen; Kong-Yang Zhu; Xiu-Bin Lin; Qin-Yan Wang; Hong-Dan Deng; Xiao-Gan Cheng (Precambrian Research, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

Pyrite coupled with steel slag to enhance simultaneous nitrogen and phosphorus removal in constructed wetlands - Ying Liu; Xiao-Hui Liu; Hong-Cheng Wang; Zhi-Ling Li; Bin Liang; Yi-Lu Sun; Hao-Yi Cheng; Shao-Yong Lu; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Microglial Depletion does not Affect the Laterality of Mechanical Allodynia in Mice - Quan Ma; Dongmei Su; Jiantao Huo; Guangjuan Yin; Dong Dong; Kaifang Duan; Hong Cheng; Huiling Xu; Jiao Ma; Dong Liu; Bin Mou; Jiyun Peng; et al. (Neuroscience Bulletin, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Parameter Study on How the Cervical Disc Degeneration Affects the Segmental Instantaneous Centre of Rotation - Hong Zhang; Dacheng Sang; Bin Zhang; Ya-Nan Ren; Xin Wang; Jing-Jing Feng; Cheng-Fei Du; Baoge Liu; Rui Zhu (Journal of Medical and Biological Engineering, 2023)

Impact of plant community structure and its diversity on richness and abundance of arthropod aphidophagous natural enemy community - Jian-hong Wang; Bin-bin Ren; Jin-li Shao; Wei Li; Shao-cheng Che (Urban Forestry & Urban Greening, 2023)

Transformation of hydroxylamine to nitrosated and nitrated products during advanced oxidation process - Zi-jun Dong; Cheng-chun Jiang; Yue Zhou; Jie-bin Duan; Li-hong Wang; Su-yan Pang; Jin Jiang; Xiao-hui Sun (Journal of Hazardous Materials, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Life cycle assessment of integrated bioelectrochemical-constructed wetland system: environmental sustainability and economic feasibility evaluation - Ying-Ke Fang; Hong-Cheng Wang; Pan-Hao Fang; Bin Liang; Kun Zheng; Qi Sun; Xi-Qi Li; Ran Zeng; Ai-Jie Wang (Resources, Conservation and Recycling, 2023)

The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods - Bai-Hong An; Da-Mao Xu; Rui Geng; Yan Cheng; Rui-Bo Qian; Xian-Chun Tang; Zhi-Qiang Fan; Hong-Bin Chen (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Early Paleozoic collision-related structures in the Tarim Craton, NW China: Implications for the Proto-Tethys evolution - Yue-Jun Li; Yong-Jin Gao; Hui Zhou; Guang-Ya Zhang; Lei Wen; Yan Zhao; Cheng Li; Duo-Ming Zheng; Ya-Lei Liu; Hong-Hui Li; Cai-Ming Luo; Tong-Fei Huang; et al. (Journal of Asian Earth Sciences, 2023)

Relation of Carotid Plaque Features Detected with Ultrasonography-Based Radiomics to Clinical Symptoms - Zhe Huang; Xue-Qing Cheng; Hong-Yun Liu; Xiao-Jun Bi; Ya-Ni Liu; Wen-Zhi Lv; Li Xiong; You-Bin Deng (Translational Stroke Research, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Association of caffeine and caffeine metabolites with obesity among children and adolescents: National Health and Nutrition Examination Survey (NHANES) 2009–2014 - Linling Yu; Hong Mei; Da Shi; Xing Wang; Man Cheng; Lieyang Fan; Yang Xiao; Ruyi Liang; Bin Wang; Meng Yang; Weihong Chen (Environmental Science and Pollution Research, 2022)

Short-term effects and economic burden assessment of ambient air pollution on hospitalizations for schizophrenia - Yanhu Ji; Bin Liu; Jian Song; Rubing Pan; Jian Cheng; Heng Wang; Hong Su (Environmental Science and Pollution Research, 2022)

Fiber-optic wireless sensor network using ultra-weak fiber Bragg gratings for vertical subsurface deformation monitoring - Su-Ping Liu; Bin Shi; Kai Gu; Cheng-Cheng Zhang; Jian-Hui He; Jing-Hong Wu; Guang-Qing Wei (Natural Hazards, 2021)

Genome-wide identification and expression analysis of glycosyltransferase gene family 1 in Quercus robur L. - Jie Zhang; Li-Mei Lin; Wen-Wen Cheng; Xin Song; Yue-Hong Long; Zhao-Bin Xing (Journal of Applied Genetics, 2021)

Particulate matter pollution associated with schizophrenia hospital re-admissions: a time-series study in a coastal Chinese city - Yanhu Ji; Bin Liu; Jian Song; Rubing Pan; Jian Cheng; Hong Su; Heng Wang (Environmental Science and Pollution Research, 2021)

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Short-term associations between ambient fine particulate matter pollution and hospital visits for chronic obstructive pulmonary disease in Yinzhou District, China - Cheng-yi Lin; Die Li; Jie-ming Lu; Zhe-bin Yu; Yao Zhu; Peng Shen; Meng-ling Tang; Ming-juan Jin; Hong-bo Lin; Li-ming Shui; Kun Chen; Jian-bing Wang (Environmental Science and Pollution Research, 2020)

High-frequency direct shoot organogenesis from garlic (Allium sativum L.) inflorescence and clonal fidelity assessment in regenerants - Yan-Bin Wen; Xiao-Xue Liu; Hong-Jiu Liu; Cui-Nan Wu; Huan-Wen Meng; Zhi-Hui Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Effect of Apolipoprotein E Genotypes on Huntington’s Disease Phenotypes in a Han Chinese Population - Xiao-Yan Li; Yan-Bin Zhang; Miao Xu; Hong-Rong Cheng; Yi Dong; Wang Ni; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

Identification of a novel strain, Streptomyces blastmyceticus JZB130180, and evaluation of its biocontrol efficacy against Monilinia fructicola - Mi Ni; Qiong Wu; Hong-li Wang; Wei-cheng Liu; Bin Hu; Dian-peng Zhang; Juan Zhao; De-wen Liu; Cai-ge Lu (Journal of Zhejiang University-SCIENCE B, 2019)

Complete Genome Sequence of Clostridium kluyveri JZZ Applied in Chinese Strong-Flavor Liquor Production - Yansheng Wang; Bin Li; Hong Dong; Xunduan Huang; Ruiyu Chen; Xingjie Chen; Laoji Yang; Bing Peng; Guopai Xie; Wei Cheng; Biao Hao; Changrun Li; et al. (Current Microbiology, 2018)

VPS9 domain‐containing proteins are essential for autophagy and endocytosis in Pyricularia oryzae - Xue‐Ming Zhu; Shuang Liang; Huan‐Bin Shi; Jian‐Ping Lu; Bo Dong; Qian‐Sheng Liao; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2018)
Summary Pyricularia oryzae is the causal pathogen of rice blast disease. Autophagy has been shown to play important roles in P . oryzae development and plant infection. The P. oryzae endosomal system is highly dynamic and has been shown to be associated with conidiogenesis and pathogenicity as well. To date, the crosstalk between autophagy and endocytosis has not been explored in P. oryzae . Here, we identified three P. oryzae VPS9 domain‐containing proteins, PoVps9, PoMuk1 and PoVrl1. We found that PoVps9 and PoMuk1 are localized to vesicles and are each co‐localized with PoVps21, a recognized marker of early endosomes. Deletion of PoVPS9 resulted in severe defects in endocytosis and autophagosome degradation and impaired the localization of PoVps21 to endosomes. Additionally, deletion of the PoMUK1 gene in the Δ Povps9 mutant background exhibited more severe defects in development, autophagy and endocytosis compared with the Δ Povps9 mutant. Pull‐down assay showed that PoVps9 interacts with PoVps21, PoRab11 and PoRab1, which have been verified to participate in endocytosis. Furthermore, yeast two‐hybrid and co‐immunoprecipitation assays confirmed that PoVps9 directly interacts with the GDP form of PoVps21. Thus, PoVps9 is a key protein involved in autophagy and in endocytosis.

Analysis of fecal microbiota in patients with functional constipation undergoing treatment with synbiotics - Lin Sheng Huang; Cheng Kong; Ren Yuan Gao; Xuebing Yan; Hong Jing Yu; Bin Wen; Qi Zhu; Tong Yi Shen; Zhen Liang Sun; Huan Long Qin (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Midazolam prevents motor neuronal death from oxidative stress attack mediated by JNK-ERK pathway - Guo-zheng Li; Hong-Lei Tao; Cheng Zhou; Dong-dong Wang; Cong-bin Peng (Human Cell, 2018)

Prediction of one-dimensional compression behavior of Nansha clay using fractional derivatives - Hong-Hu Zhu; Cheng-Cheng Zhang; Guo-Xiong Mei; Bin Shi; Lei Gao (Marine Georesources & Geotechnology, 2017)

Effect of culture conditions on metabolites produced by the crinoid-derived fungus Aspergillus ruber 1017 - Yong-Fang Li; Xue-Bin Wu; Shah-Iram Niaz; Liu-Hong Zhang; Zhi-Jian Huang; Yong-Cheng Lin; Jing Li; Lan Liu (Natural Product Research, 2017)

MoRad6‐mediated ubiquitination pathways are essential for development and pathogenicity in Magnaporthe oryzae - Huan‐Bin Shi; Guo‐Qing Chen; Ya‐Ping Chen; Bo Dong; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2016)
Summary The ubiquitin system modulates protein functions through targeting substrates for ubiquitination. Here, E2 conjugating enzyme MoRad6‐related ubiquitination pathways are identified and analyzed in Magnaporthe oryzae , the causal agent of rice blast disease. Disruption of MoRad6 leads to severe defects in growth, sporulation, conidial germination, appressorium formation, and plant infection. To depict the functions of MoRad6, three putative ubiquitin ligases, MoRad18, MoBre1 and MoUbr1, are also characterized. Deletion of MoRad18 causes minor phenotypic changes, while MoBre1 is required for growth, conidiation and pathogenicity in M. oryzae . Defects in ΔMobre1 likely resulted from the reduction in di‐ and tri‐methylation level of Histone 3 lysine 4 (H3K4). Notably, MoUbr1 is crucial for conidial adhesion and germination, possibly by degrading components of cAMP/PKA and mitogen‐activated protein kinase (MAPK) Pmk1 signaling pathways via the N‐end rule pathway. Germination failure of ΔMoubr1 conidia could be rescued by elevation of cAMP level or enhanced Pmk1 phosphorylation resulting from further deletion of MoIra1, the M. oryzae homolog of yeast Ira1/2. These reveal vital effects of cAMP/PKA and MAPK Pmk1 signaling on conidial germination in M. oryzae . Altogether, our results suggest that MoRad6‐mediated ubiquitination pathways are essential for the infection‐related development and pathogenicity of M. oryzae .

Programmed cell death in the cyanobacterium Microcystis aeruginosa induced by allelopathic effect of submerged macrophyte Myriophyllum spicatum in co-culture system - Yan He; Qiao-Hong Zhou; Bi-Yun Liu; Long Cheng; Yun Tian; Yong-Yuan Zhang; Zhen-Bin Wu (Journal of Applied Phycology, 2016)

Climate change and glacier area variations in China during the past half century - Hong-zhen Tian; Tai-bao Yang; Hui Lv; Cheng-xiu Li; Ying-bin He (Journal of Mountain Science, 2016)

Lentzea guizhouensis sp. nov., a novel lithophilous actinobacterium isolated from limestone from the Karst area, Guizhou, China - Cheng-Liang Cao; Xiao-Qi Zhou; Sheng Qin; Fa-Xiang Tao; Ji-Hong Jiang; Bin Lian (Antonie van Leeuwenhoek, 2015)

The small GTP ase MoYpt 7 is required for membrane fusion in autophagy and pathogenicity of M agnaporthe oryzae - Xiao‐Hong Liu; Si‐Miao Chen; Hui‐Min Gao; Guo‐Ao Ning; Huan‐Bin Shi; Yao Wang; Bo Dong; Yao‐Yao Qi; Dong‐Mei Zhang; Guo‐Dong Lu; Zong‐Hua Wang; Jie Zhou; et al. (Environmental Microbiology, 2015)
Summary R ab GTP ases are required for vesicle–vacuolar fusion during vacuolar biogenesis in fungi. To date, little is known about the biological functions of the R ab small GTP ase components in M agnaporthe oryzae . In this study, we investigated MoYpt 7 of M . oryzae , a homologue of the small R as‐like GTP ase Ypt7 in S accharomyces cerevisiae . Cellular localization assays showed that MoYpt 7 was predominantly localized to vacuolar membranes. Using a targeted gene disruption strategy, a Δ MoYPT7 mutant was generated that exhibited defects in mycelial growth and production of conidia. The conidia of the Δ MoYPT7 mutant were malformed and defective in the formation of appressoria. Consequently, the Δ MoYPT7 mutant failed to cause disease in rice and barley. Furthermore, the Δ MoYPT7 mutant showed impairment in autophagy, breached cell wall integrity, and higher sensitivity to both calcium and heavy metal stress. Transformants constitutively expressing an active MoYPT7 allele ( MoYPT7 ‐ CA , G ln67 L eu) exhibited distinct phenotypes from the Δ MoYPT7 mutant. Expression of MoYPT7 ‐ CA in MoYpt 7 reduced pathogenicity and produced more appressoria‐forming single‐septum conidia. These results indicate that MoYPT7 is required for fungal morphogenesis, vacuole fusion, autophagy, stress resistance and pathogenicity in M . oryzae .

Effects of pre-harvest chemical application on rice desiccation and seed quality - Yong-qi He; Jin-ping Cheng; Liang-feng Liu; Xiao-dan Li; Bin Yang; Hong-sheng Zhang; Zhou-fei Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Assessment of a Four-View Mammographic Image Feature Based Fusion Model to Predict Near-Term Breast Cancer Risk - Maxine Tan; Jiantao Pu; Samuel Cheng; Hong Liu; Bin Zheng (Annals of Biomedical Engineering, 2015)

Functional characterization of a chalcone synthase from the liverwort Plagiochasma appendiculatum - Hai-Na Yu; Lei Wang; Bin Sun; Shuai Gao; Ai-Xia Cheng; Hong-Xiang Lou (Plant Cell Reports, 2015)

A cell-based model of bone remodeling for identifying activity of icarrin in the treatment of osteoporosis - Yan-Qiu Liu; Xiao-Fei Han; Tiegang Liu; Meng-Chun Cheng; Hong-Bin Xiao (Biotechnology Letters, 2015)

Distributed fiber optic monitoring and stability analysis of a model slope under surcharge loading - Hong-Hu Zhu; Bin Shi; Jie Zhang; Jun-Fan Yan; Cheng-Cheng Zhang (Journal of Mountain Science, 2014)

Aroma types of flue-cured tobacco in China: spatial distribution and association with climatic factors - Chao Yang; Wei Wu; Shu-Cheng Wu; Hong-Bin Liu; Qing Peng (Theoretical and Applied Climatology, 2014)

Assessment of wheat variety stability using SSR markers - Li Xin Wang; Hong Bo Li; Tie Cheng Gu; Li Hua Liu; Bin Shuang Pang; Jun Qiu; Chang Ping Zhao (Euphytica, 2014)

The discovery of 3-(1-aminoethylidene)quinoline-2, 4(1H,3H)-dione derivatives as novel PSII electron transport inhibitors - Yu-Xiu Liu; Hua-Ping Zhao; Zi-Wen Wang; Yong-Hong Li; Hai-Bin Song; Hannah Riches; David Beattie; Yu-Cheng Gu; Qing-Min Wang (Molecular Diversity, 2013)

Erratum to: UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

An Intronic CYP46A1 Polymorphism Is Associated with Alzheimer Disease in a Chinese Han Population - Xiao-ming He; Zhen-xin Zhang; Jun-wu Zhang; Yong-tao Zhou; Cheng-bin Wu; Mou-ni Tang; Zhen Hong (Journal of Molecular Neuroscience, 2012)

Mapping QTLs with epistatic effects and QTL × treatment interactions for salt tolerance at seedling stage of wheat - Yun-Feng Xu; Diao-Guo An; Dong-Cheng Liu; Ai-Min Zhang; Hong-Xing Xu; Bin Li (Euphytica, 2012)

Identification and expression analysis of four 14-3-3 genes during fruit ripening in banana (Musa acuminata L. AAA group, cv. Brazilian) - Mei-Ying Li; Bi-Yu Xu; Ju-Hua Liu; Xiao-Liang Yang; Jian-Bin Zhang; Cai-Hong Jia; Li-Cheng Ren; Zhi-Qiang Jin (Plant Cell Reports, 2012)

Synthesis of Benzimidazoles Containing Pyrazole Group and Quantum Chemistry Calculation of Their Spectroscopic Properties and Electronic Structure - Ren Tie-gang; Cheng Hong-bin; Zhang Jing-lai; Li Wei-jie; Guo Jia; Yang Li-rong (Journal of Fluorescence, 2012)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Expressions of CXCR7/ligands may be involved in oral carcinogenesis - Juan Xia; Juan Wang; Na Chen; Yaohui Dai; Yun Hong; Xiaobing Chen; Bin Cheng (Journal of Molecular Histology, 2011)

Identification of Components of the Female Sex Pheromone of the Simao Pine Caterpillar Moth, Dendrolimus kikuchii Matsumura - Xiang-Bo Kong; Xiao-Ling Sun; Hong-Bin Wang; Zhen Zhang; Cheng-Hua Zhao; Kees C. J. H. Booij (Journal of Chemical Ecology, 2011)

Expression of gap junctional protein connexin43 during 4-nitroquinoline-1-oxide-induced rat tongue carcinogenesis - Juan Xia; Xiumei Liu; Xiaoan Tao; Yun Hong; Xiaobing Chen; Yaohui Dai; Yulei Huang; Bin Cheng (Journal of Molecular Histology, 2009)

Detection of the key enzyme of alginate biosynthesis in Vibrio sp. QY102 - Xiao-Chong Shi; Qian-Hong Gong; Ru-Bin Cheng (World Journal of Microbiology and Biotechnology, 2008)

Morphological observation of nuclear sub-localization of human angiogenin in HUVECs - Jie Wu; Hong-Bin Zhang; Jie Wang; Tai-Cheng Yang; Jiang Xian; Chuan-Hong Yang; Huang-Wen Lai (Biotechnology Letters, 2008)

Polymorphisms in intron 1 of the porcinePOU1F1 gene - Cheng-Yi Song; Bo Gao; Shang-Hui Teng; Xiao-Yang Wang; Fei Xie; Guo-hong Chen; Zhi-Yue Wang; Rong-bin Jing; Jiu-De Mao (Journal of Applied Genetics, 2007)

Female Sex Pheromone of the Yunnan Pine Caterpillar Moth Dendrolimus Houi: First (E,Z)-Isomers in Pheromone Components of Dendrolimus spp - Xiang Bo Kong; Zhen Zhang; Cheng Hua Zhao; Hong Bin Wang (Journal of Chemical Ecology, 2007)

Capillary gas chromatographic determination of dimethachlon residues in fresh tobacco leaves and cut-tobacco - Hong-cheng Liu; Qi-wan Li; Li-bin Tang (Journal of Zhejiang University-SCIENCE B, 2007)

Removal of dibutyl phthalate by a staged, vertical-flow constructed wetland - Wen Yu Zhao; Zhen Bin Wu; Qiao Hong Zhou; Shui Ping Cheng; Gui Ping Fu; Feng He (Wetlands, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)